Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1007/bf01400670
|View full text |Cite
|
Sign up to set email alerts
|

Open thrombectomy combined with thrombolysis in massive intracranial sinus thrombosis

Abstract: A case of complete thrombosis of the superior sagittal sinus in a pregnant women with multiple haemorrhages and hydrocephalus is described. Due to acute onset and progressive neurological deterioration, the decision was taken to remove the clot surgically. A sinotomy was performed removing the thrombotic material followed by local infusion of tissue plasminogen activator (t-PA). The combination of surgical removal and thrombolysis was life-saving for this young patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 8 publications
0
9
0
5
Order By: Relevance
“…Therefore, 72 studies [6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77], totalling 169 patients were included in the review. Ten studies reported on 5 or more patients (89 patients), the largest case series with 18 patients [71].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 72 studies [6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77], totalling 169 patients were included in the review. Ten studies reported on 5 or more patients (89 patients), the largest case series with 18 patients [71].…”
Section: Resultsmentioning
confidence: 99%
“…The use of direct surgical thrombectomy or venous sinus bypass has been described by several authors [35, 36, 37, 38, 39]. Although these techniques may result in dramatic improvement, they are associated with tremendous risk in the small child or neonate.…”
Section: Discussionmentioning
confidence: 99%
“…With treatment the long-term prognosis for most patients with CVST is good, though a small percentage die or are left with significant disability [2]. Hydrocephalus from CVST is rare, and this patient represents the fifth case published in the English language literature [4][5][6].…”
Section: Discussionmentioning
confidence: 98%